Determinants of organic food purchasing intention: an empirical study of local consumers in Da Nang city, Central Vietnam - Mai, Ngo Thanh; Phuong, Tran Thi Lan; Dat, Tran Tho; Truong, Dinh Duc (Frontiers in Sustainable Food Systems, 2023)
With the rapid economic development in the past decades, Vietnamese people are more and more aware of the role of safe food for their health and that of their families. Currently, the trend of organic food consumption is happening faster, especially in urban areas. The study aims to determine the influence of transparent information and knowledge about organic products on consumers' attitudes, trust, and subjective norms affecting their purchase intention of organic products. Data were collected from 420 consumers in Da Nang city, Central Vietnam. Exploratory Factor Analysis (EFA) method and Structural Equation Modeling (SEM) were used to evaluate the scale's reliability and identify the impact factors. The results show that attitudes and trust have a positive relationship with the intention to buy organic food. In addition, research shows that trust is a predecessor of attitudes and mediates the relationship between information, knowledge about organic food, and intention to buy organic food. The study's findings are consistent with previous literature and provide implications for food managers, organic food businesses and the community.